If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7g + -3y + 11w + 4y + -2w + 4g = 0 Reorder the terms: 7g + 4g + 11w + -2w + -3y + 4y = 0 Combine like terms: 7g + 4g = 11g 11g + 11w + -2w + -3y + 4y = 0 Combine like terms: 11w + -2w = 9w 11g + 9w + -3y + 4y = 0 Combine like terms: -3y + 4y = 1y 11g + 9w + 1y = 0 Solving 11g + 9w + 1y = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-9w' to each side of the equation. 11g + 9w + -9w + 1y = 0 + -9w Combine like terms: 9w + -9w = 0 11g + 0 + 1y = 0 + -9w 11g + 1y = 0 + -9w Remove the zero: 11g + 1y = -9w Add '-1y' to each side of the equation. 11g + 1y + -1y = -9w + -1y Combine like terms: 1y + -1y = 0 11g + 0 = -9w + -1y 11g = -9w + -1y Divide each side by '11'. g = -0.8181818182w + -0.09090909091y Simplifying g = -0.8181818182w + -0.09090909091y
| 3x+25+20=180 | | 3x-25=90 | | 4x+2(3x)=40 | | z-8z=5z-2-z | | 11x+3=5x-3 | | 9x+6y+33=0 | | 3x+25=90 | | 10x-2(3x-5)=26 | | 4y=y-3 | | 8x-2(x+1)=2(3x+1) | | 13+y=l+y | | 3(7-x)=10 | | 20x^3-17x^2=-3x | | z-6z=9z-3-z | | 6x^2+66x-180=0 | | (x^5+7x-3)+(x^3+8x+10)-(x^8-17)= | | 10(x+13)+50x+20(2x+2)=1670 | | 1.4x^2=5.6 | | 11(a-5)=-4-7 | | 2y^2-36y^1+162y=0 | | (4.9-2.2)(3.4+0.4)= | | 42+-2x=4 | | 3(x+1)+2(x-1)=0 | | 4-12x+39x-18x=256-60x-657x | | 2M+20=M+80 | | 6.2=10x+7.9 | | 0.10x+0.25(x+6)+0.05(3)(x+6)=7.40 | | 4x(x-2)-10x=-40 | | 0.25y+5=28 | | 500x-0.05=700x+0.73 | | 6x-8+12x=62 | | 2x+y-2z-8=0 |